Prediction of difficult endotracheal intubation by different bedside tests: An observational study - Kirti Kamal; Divya Rani; Geeta Ahlawat; Teena Bansal (Bali Journal of Anesthesiology, 2023)
Background: An incidence of difficult intubation in elective surgery is 1.5%–8%. Multiple attempts during tracheal intubation can cause airway injuries bleeding, brain hypoxia, and even cardiac arrest. Unanticipated failure and inability to secure difficult airway can lead to “cannot ventilate, cannot intubate” condition. Preoperative assessment and bedside tests play a vital role in predicting and stratifying risk of difficult intubation. This study was done to determine the incidence of difficult intubation and diagnostic accuracy of different bedside tests for predicting intubation difficulty in patients without airway pathology scheduled for elective surgery under general anesthesia. Materials and Methods: Two hundred patients, aged 20–50 years, American Society of Anaesthesiologists I and II, without airway pathology undergoing elective surgery were evaluated preoperatively using simple bedside tests such as Mallampati grading (MPG), interincisor gap (IIG), thyromental distance (TMD), sternomental distance, upper lip bite test, neck circumference, and atlantooccipital extension to predict difficult intubation. Statistical confirmation was done using Pearson’s chi-square test and univariate and multivariate logistic regression. Results: In our study, the incidence of difficult intubation was observed as 6%. High sensitivity for predicting difficult intubation was seen with IIG > TMD > MPG, and high specificity among the relevant bedside tests was seen with TMD > MPG > IIG. Tests with high positive predictive value were TMD > MPG, whereas high negative predictive value was seen with IIG > TMD >MPG. Conclusion: IIG, TMD, and MPG can be used to predict difficult intubation in patients without airway pathology.